2021
DOI: 10.1111/jmft.12492
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of acceptance and commitment therapy (ACT) on emotional regulation and loneliness of divorced women in Iran

Abstract: Ineffective emotional regulation and loneliness both play a key role in the development of mental disorders. Divorced individuals are particularly predisposed to loneliness in cultures where post‐divorce relationships are uncommon or stigmatized. The aim of the present study was to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on the emotional regulation and loneliness of divorced women in Iran, a culture with strong honor values that condemn post‐divorce relationships for women leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 37 publications
5
22
0
Order By: Relevance
“…These findings were consistent with the results of previous studies. [27][28][29][30][31][32] According to Hayes and Strosahl, 33 as a person enters the ACT process, their involvement in negative mental-verbal processes focusing on themselves and others improves and changes gradually. In the ACT, healing can be well enhanced through avoiding anxiety and worry, freeing oneself from the past and bitter experiences, living in the present, and emphasizing values and committed action to reduce stress.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the results of previous studies. [27][28][29][30][31][32] According to Hayes and Strosahl, 33 as a person enters the ACT process, their involvement in negative mental-verbal processes focusing on themselves and others improves and changes gradually. In the ACT, healing can be well enhanced through avoiding anxiety and worry, freeing oneself from the past and bitter experiences, living in the present, and emphasizing values and committed action to reduce stress.…”
Section: Discussionmentioning
confidence: 99%
“…The most important finding of this study was the verification of hypothesis 3. Some studies have shown that emotion regulation is associated with loneliness ( 64 , 65 ). However, in this study, only expressive suppression moderated the relationship between hope and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…This social situation for divorced women is accompanied by fear of loneliness, and also the sense of being humiliated by family and friends (Sabour Esmaeili et al, 2015). Iranian divorced women face various cultural and social restrictions (Mahmoudpour et al, 2021). Under such circumstances, children of such mothers are at increased risk of adverse outcomes following a family breakdown and the negative outcomes can persist from childhood into adulthood (Hasse et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, 2015). Iranian divorced women face various cultural and social restrictions (Mahmoudpour et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%